Effects of cellulase and Lactiplantibacillus plantarum on the fermentation quality, microbial diversity, gene function prediction, and in vitro rumen fermentation parameters of Caragana korshinskii silage - Ju, Ji; Zhang, Guijie; Xiao, Ming; Dong, Chenyang; Zhang, Runze; Du, Liu; Zheng, Yongjie; Wei, Manli; Wei, Manlin; Wu, Baiyila (Frontiers in Food Science and Technology, 2023)
In the present study, we investigated the effects of cellulase and Lactiplantibacillus plantarum (L. plantarum) on the fermentation quality, microbial diversity, gene function prediction, and in vitro rumen fermentation parameters of the Caragana korshinskii (C. korshinskii) silage. The experimental treatment groups included control (CK), cellulase (C), L. plantarum (L), and cellulase + L. plantarum (CL). Triplicate silos were sampled after 14 and 56 days of ensiling. The microbial diversity of C. korshinskii silage at 56 days was analyzed using Illumina MiSeq sequencing technology, and the effects of C. korshinskii silage on rumen fermentation were evaluated by the in vitro artificial rumen gas production method. The results showed that the addition of cellulose and L. plantarum treatments reduced ammonia-nitrogen (NH3-N), dry matter (DM), neutral detergent fiber (NDF), and acid detergent fiber content during ensiling. Compared with the CK group, higher lactic acid content was observed in the silage of the C and L groups, but the CL group had a higher acetic acid (AA) content. Compared with the CK group, the relative abundance of Lactiplantibacillus significantly increased, but that of Enterococcus, Weissella, Enterobacter, and Pediococcus significantly decreased in all other groups except the C group (p < 0.05). The results of gene function prediction were as follows: pyruvate kinase, 1-phosphofructokinase, and fructokinase were lactate production enzymes, which suggested the association of the high AA content in the CL group to the high abundance of 6-phosphate glucose dehydrogenase. The abundance of H + -transporting ATPase and ATP-binding cassette (ABC) transporters in the L and CL groups was higher than that in the CK groups. Metabolism of terpenoids and polyketides, mismatch repair, DNA replication, nucleotide excision repair, and homologous recombination increased in the CL group compared with those in the CK group. Compared with the CK group, NH3-N and microbial protein content and the degradation rates of DM and NDF increased in the L and CL groups. To conclude, the L and CL groups had increased Lactiplantibacillus abundance, improved fermentation quality, and high DM degradation rates compared with the CK group.